Exploring assistive technology as a potential beneficial intervention tool for people with Alzheimer's disease - a systematic review - Klimova, Blanka; Valis, Martin; Kuca, Kamil (Neuropsychiatric disease and treatment, 2018)
Nowadays, due to the increase in the number of aging population groups, there is also a growth of aging diseases such as Alzheimer's disease (AD), which is a progressive brain disorder that eventually results in death. At the moment, it cannot be cured, only its symptoms can be alleviated both by using pharmacological and non-pharmacological approaches in order to maintain and in some cases even enhance quality of life of people living with AD, as well as their caregivers. One of such non-pharmacological approaches is the use of assistive technology (AT), which can contribute to the improvement and maintenance of the quality of life of both patients and their caregivers. The purpose of this study was to explore what types of AT are mostly used by patients with AD and how these devices can help their caregivers. This was done by conducting a literature review of available sources found in the Web of Science, Scopus, and PubMed. The findings, apart from one study, reveal that AT may have the potential to maintain the quality of life of people with AD, especially in the early stages of the disease, as well as to mitigate the mental and physical burden of their caregivers. The most common types of AT for patients with AD are devices of daily living and safety devices. The less frequent are still telecare devices and devices to support engagement, social participation, and leisure. Future research should focus on the effectiveness of AT on the improvement of patients' symptoms, as well as on the development and use of AT for social interactions, which can be used in patients with AD of different degree of severity and have a positive impact on their behavioral and psychological symptoms.
Keywords: assistive technology; patients; caregivers; benefits; Alzheimer’s disease